The politics of influence : British ex-servicemen, Cabinet decisions and cultural change, 1917-57 - Wootton, Graham (London : Routledge, 1998)
First published in 1998.
Appendix 5. Letter from Minister of Pensions to Chairman of BLESMA All-Party Parliamentary Committee, 1956Appendix 6. Appealing to Public Opinion: the British Legion, 1953; Index of Names; Index of Subjects.
Includes index.
Print version record.
eBooks on EBSCOhost
Keywords: Veterans -- Great Britain; Great Britain -- Politics and government -- 20th century; Anciens combattants -- Grande-Bretagne.; Grande-Bretagne -- Politique et gouvernement -- 20e siècle.; HISTORY -- Military -- Other; TECHNOLOGY & ENGINEERING -- Military Science; Politics and government; Veterans; Great Britain; 1900-1999; Electronic book